Flowering Locus C (FLC) Is a Potential Major Regulator of Glucosinolate Content across Developmental Stages of Aethionema arabicum (Brassicaceae) - Mohammadin, Setareh; Nguyen, Thu-Phuong; van Weij, Marco S.; Reichelt, Michael; Schranz, Michael E. (Frontiers in Plant Science, 2017)
The biochemical defence of plants can change during their life-cycle and impact herbivore feeding and plant fitness. The annual species Aethionema arabicum is part of the sister clade to all other Brassicaceae. Hence, it holds a phylogenetically important position for studying crucifer trait evolution. Glucosinolates are essentially Brassicales-specific metabolites involved in plant defence. Using two Ae. arabicum accessions (TUR and CYP) we identify substantial differences in glucosinolate profiles and quantities between lines, tissues and developmental stages. We find tissue specific side-chain modifications in aliphatic glucosinolates: methylthioalkyl in leaves, methylsulfinylalkyl in fruits and methylsulfonylalkyl in seeds. We also find large differences in absolute glucosinolate content between the two accessions (up to ten-fold in fruits) that suggest a regulatory factor is involved that is not part of the quintessential glucosinolate biosynthetic pathway. Consistent with this hypothesis, we identified a single major multi-trait QTL (Quantitative Trait Locus) controlling total GS concentration across tissues in a Recombinant Inbred Line (RIL) population derived from TUR and CYP. With fine-mapping, we narrowed the interval to a 58kb region containing fifteen genes, but lacking any known GS biosynthetic genes. The interval contains homologs of both the sulphate transporter SULTR2;1 and FLOWERING LOCUS C (FLC). Both loci have diverse functions controlling plant physiological and developmental processes and thus are potential candidates regulating glucosinolate variation across the life-cycle of Aethionema. Future work will investigate changes in gene expression of the candidates genes, the effects of GS variation on insect herbivores and the trade-offs between defense and reproduction.